Electrochemical methods in archaeometry, conservation and restoration - Carbó, Antonio Doménech (Springer, 2013)
Electrochemistry plays an important role in preserving our cultural heritage. For the first time this has been documented in the present volume. Coverage includes both electrochemical processes such as corrosion and electroanalytical techniques.